EVALUASI KUALITAS SEMEN BEKU BABI LANDRACE DALAM PENGENCER SPERMAX MODIFIKASI DENGAN WAKTU PRE-FREEZING YANG BERBEDA (Assessment of Landrace Boar Frozen Semen Quality in Modified Spermax Diluent Under Varying Pre-freezing Durations) - Kii, Mariana B.I.; Hine, Thomas M; Bette, Yustiany Y; Nalley, Wilmientje M (Universitas Nusa Cendana, 2025)
Research was conducted to investigate the impact of different pre-freezing durations (PF) using a modified spermax (M) extender on the quality of frozen landrace boar semen. The study utilized fresh semen from four healthy Landrace boars aged 2-3 years. Fresh semen meeting SNI standards was diluted in SM extender and held at room temperature (27-28℃) for two hours. Subsequently, the semen was centrifuged at 2000 rpm for 10 minutes, the supernatant was discarded, and the sperm pellet was re-diluted with SM extender at a 1:1 ratio. The semen was then packaged in 0.5 mL straws, placed on a freezing rack, and allowed to equilibrate for two hours at 3-5℃. Following equilibration, the semen was re-evaluated, and the straws were frozen above liquid nitrogen at -110℃ with varying pre-freezing times of 5, 8, 11, and 14 minutes. After the pre-freezing period, the straws were plunged into liquid nitrogen for final freezing and then stored in liquid nitrogen containers at -196℃. The results indicated that the duration of pre-freezing time did not lead to statistically significant differences (P>0,05) in sperm motility, viability, abnormality, and recovery rate (RR). In conclusion, pre-freezing times ranging from 5 to 14 minutes had a similar impact on the quality of frozen landrace boar semen.